"Evaluación de la calidad bromatológica y sensorial de galletas con sustitución parcial de harina trigo (Triticum spp) por amaranto (Amaranthis spp)". - Carrillo Pisco, María Laura (2020)
The purpose of this research was to evaluate the sensory, bromatological and microbiological quality of cookies with partial replacement of wheat flour (Triticum spp) with amaranth (Amaranthus spp). A Completely Random AxB Design was applied to the three best treatments that resulted from the sensory analysis with five repetitions. To determine the differences between the treatments, the Tukey multiple range test was used at 5% probability. Bromatological variables (humidity, ash, ethereal extract, total nitrogen, crude fiber, and ELnN), microbiological variables (mesophilic aerobes and molds - yeasts), sensory variables (color, odor, taste, texture and general acceptability) and economic variables were analyzed. (profitability and cost of production). The results of the Sensory analysis showed that the T1, T3 and T7 obtained greater acceptance in the tributes of flavor, color, texture, smell and acceptability; Based on the bromatological analysis, it was determined that the T7 of the formulation of partial replacement of 20% wheat flour with amaranth flour was the best treatment with 2.94% humidity; ash with 2.31%, 17.84% fat, 4.69% fiber, 8.37% protein, 63.85% ELnN. The microbiological analysis reflected the absence of mesophilic aerobes and molds - yeasts, complying with the regulations guaranteeing food safety. The cost of production was $ 4.08 with a yield of 200 cookies of 5gr each on a dry basis and a profit margin of 30%. The research was carried out in the Laboratory of Food Bromatology and Microbiology of the Faculty of Livestock Sciences, ESPOCH, in the Riobamba canton of Cotopaxi, Ecuador. Key words: Amaranth, cookies, flour, substitution, percentages.